RANCANGAN ATRAKSI WISATA EDUKASI DI KAMPUNG HIJAU KOTA BANJARMASIN - Riadi, Selamat; Normelani, Ellyn; Bachri, Ahmad Alim; Hidayah, Nur; Sari, Yulika Puspita (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2020)
Banjarmasin city is a popular tourist destination for its river tourism. One of the tourist destinations that offer a distinctive atmosphere of river-based Banjar culture is Kampung Hijau. This tourist attraction is located on the Martapura river banks, which was developed with a Community-based Tourism (CBT) approach. This study aims to design educational tourist attractions in the Kampung Hijau tourist destination. This study uses a qualitative approach with descriptive types. Data collection was carried out by the survey, interview, and documentation study. The design of educational tourism attractions designed in Kampung Hijau provides basic knowledge of community adaptation and mitigation actions against climate change and other matters. It increases tourist knowledge and understanding by firsthand the community's adaptation and mitigation activities.Â Keywords: Attraction; Education tourism; Kampung hijau